Susceptibility of Candida glabrata biofilms to echinocandins: alterations in the matrix composition. Issue 5 (28th May 2018) - Rodrigues, Célia F.; Rodrigues, Maria Elisa; Henriques, Mariana
Abstract: Candidiases are the most recurrent fungal infections, especially among immunosuppressed patients. Although Candida albicans is still the most widespread isolated species, non- Candida albicans Candida species have been increasing. The goal of this work was to determine the susceptibility of C. glabrata biofilms to echinocandins and to evaluate their effect on the biofilm matrix composition, comparing the results with other Candida species . Drug susceptibilities were assessed through the determination of minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC) and minimum biofilm eradication concentration (MBEC) of caspofungin (Csf) and micafugin (Mcf). The β-1, 3 glucans content of the matrices was assessed after contact with the drugs. The data suggest that, generally, after contact with echinocandins, the concentration of β-1, 3 glucans increased. These adjustments in the matrix composition of C. glabrata biofilms and the chemical differences between Csf and Mcf, seem responsible and may determine the effectivity of the drug responses.